2005
DOI: 10.5175/jswe.2005.200202122
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Among Hours Employed, Perceived Work Interference, and Grades as Reported by Undergraduate Social Work Students

Abstract: This article reports on an exploratory research study that found that working a half-time job while pursuing a full-time course load is typical for most undergraduate social work students. Average number of hours worked and perceived work interference with studies were associated with lower overall grade point average.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 18 publications
0
20
0
11
Order By: Relevance
“…However, students have also mentioned work as having a detrimental effect on their studying and on social activities (Manthei and Gilmore 2005). In line with these results, Hawkins et al (2005) found that more than half of students in their study perceived that work decreased their study time, with one-fifth of the students experiencing stress, fatigue and exhaustion from work. On the other hand, Robotham (2009) found that working enhanced students' ability to cope with stress.…”
Section: Introductionmentioning
confidence: 52%
“…However, students have also mentioned work as having a detrimental effect on their studying and on social activities (Manthei and Gilmore 2005). In line with these results, Hawkins et al (2005) found that more than half of students in their study perceived that work decreased their study time, with one-fifth of the students experiencing stress, fatigue and exhaustion from work. On the other hand, Robotham (2009) found that working enhanced students' ability to cope with stress.…”
Section: Introductionmentioning
confidence: 52%
“…Among full-time college students, nearly half (48%) work full- or part-time and almost a third (34%) of all students work > 20 h a week (Fox, Connolly, & Snyder, 2005; Hawkins, Hawkins II, Smith, & Grant, 2005). Similarly, college students who work > 20 h per week are also at risk for increased substance use, lower academic achievement, and not obtaining a degree (Astin, 1993; Furr & Elling, 2000; Hawkins et al, 2005; Paschall et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, college students who work > 20 h per week are also at risk for increased substance use, lower academic achievement, and not obtaining a degree (Astin, 1993; Furr & Elling, 2000; Hawkins et al, 2005; Paschall et al, 2004). Cross-sectional research has demonstrated a relationship between increased hours working (especially working > 20 h per week) and greater alcohol use in college student populations (Miller, Danner, & Staten, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The most significant contributing factor may be the necessity for so many community college students to work while attending classes. Working 20 hours or more a week is associated with negative effects on academic performance for college students (Furr & Elling, 2000;Hawkins, Hawkins, Smith, & Grant, 2005), which may further increase stress. Other contributing factors to high stress may include parenting while taking classes, financial worries, and health concerns (Johnson et al, 2010).…”
Section: Healthmentioning
confidence: 98%